2010
DOI: 10.12968/ijpn.2010.16.9.78636
|View full text |Cite
|
Sign up to set email alerts
|

Where do nurses go for help? A qualitative study of coping with death and dying

Abstract: As end-of-life care becomes a more prominent issue in health care, it is important to address the experience from the caregivers' perspective. In order to cope with the stressful experience of caring for a dying patient, nurses need programmes that both help them develop coping strategies and prepare them for caring for dying patients as well as resources to help them cope with the experience once it has happened. Because little is known about the coping habits of nurses facing the death of a patient, research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 27 publications
8
67
1
2
Order By: Relevance
“…Many nurses also use some form of religious resource to help cope with the death of a patient, etc. [17][18][19]. Furthermore, MacDonald and Friedman [15] argue that higher levels of spirituality correlate to a lower level of burnout in nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Many nurses also use some form of religious resource to help cope with the death of a patient, etc. [17][18][19]. Furthermore, MacDonald and Friedman [15] argue that higher levels of spirituality correlate to a lower level of burnout in nurses.…”
Section: Discussionmentioning
confidence: 99%
“…[13] supported the above statement concerning the staff who is also in need of PC/support. They showed that communicating with patients and their families, as well as with co-workers, is an integral part of how nurses cope with death and dying.…”
Section: A Personal Reportmentioning
confidence: 71%
“…(Redinbaugh et al 2003, Stedeford 1994. Being able to 'turn-off' or establish professional distance is considered a coping strategy (Hopkinson et al 2005, Shorter & Stayt 2009, Espinosa et al 2010, Kelly & Nisker 2010, Peterson et al 2010, Melvin 2012, Williams 2013). However, whilst these coping strategies may protect the healthcare professional from the cumulative effects of providing care for the dying, they do not promote quality, patient-centred compassionate care and may be deemed 'callous' and 'indifferent', as reported in the Francis Report (2013, p13).…”
Section: Contrasts In Reactionmentioning
confidence: 99%
“…Similar findings are reported by emergency workers, who felt fearful of the long-term consequences and stigmatisation of allowing themselves to respond emotionally (Halpern et al 2009). Studies have also reported that other healthcare professionals felt they had to cope with patient loss in a 'professional' manner by putting up boundaries and not over-investing in patient-carer relationships (Rhodes-Kropf et al 2005, Shorter & Stayt 2009, Gerow et al 2010, Peterson et al 2010, Melvin 2012, Williams 2013. Redinbaugh et al (2003, p327) reported that senior doctors who are reluctant to discuss their emotional responses to significant deaths "convey a message about how death is to be handled and potentially isolate learners".…”
Section: Contrasts In Reactionmentioning
confidence: 99%
See 1 more Smart Citation